International panorama of scientific production on Environmental Economics: A bibliometric study (Research, Society and Development, 2021)
The Environmental Economics has the purpose to minimize the impacts on the environment and the ecosystems. In this regard, the guidance is to maximize the value of the resources by means of a detailed analysis about the effects of the environmental deterioration, such as global warming, greenhouse effect or other negative impacts. In this context, the aim of this article was to analyze the international scientific literature about Environmental Economics indexed in the international database Web of Science. For this purpose, the methodological procedure was the bibliometric survey, using an exploratory and descriptive research, which measures the international productivity on the theme, and used the VOSviewer software version 1.6.12 to develop clusters maps, allowing a relational analysis between authors, organizations, countries, as well as highlighting the elaboration of subfields in the overall thematic. The main results pointed to a productivity development, main authors clusters, organizations and countries, in addition to indicate research areas inside the field, starting from the delimitation of the research subjects.